Proceso de atención de enfermería a paciente de 20 años de edad con embarazo molar completo. - López Aguiar, Betsy Emiliana (2021)
Molar pregnancy, also known as hydatidiform mole, is defined as a rare complication of pregnancy, characterized by the abnormal growth of trophoblasts, which are cells that normally develop in the placenta, many times it can seem like a normal pregnancy, but the Most cases cause specific signs and symptoms, such as bright red or dark brown vaginal bleeding during the first trimester, severe nausea and vomiting, pressure, or pelvic pain. It has been proven that around 80 percent of gestational trophoblastic diseases correspond to hydatidiform mole, however, its incidence for complete and partial mole is 1 to 3,1000 pregnancies respectively. It is revealed to a patient with a personal history of urinary tract infections, who went to the gynecological emergency area for presenting a clinical picture of 21 hours of evolution characterized by pain in the hypogastric region of colic type irradiated to the lumbosacral region of mild to moderate intensity plus bleeding transvaginal in a slight amount, vital signs were checked, she was assessed by the attending physician who requested a laboratory order, with a posterior anterior chest X-ray with findings of increased interstitial marks, thickening of the bronchial walls and pulmonary distension, laboratory studies were already requested. obtaining the results is diagnosed with complete molar pregnancy, prescribed medication is administered, the patient is discharged from hospital in stable clinical conditions days after surgery.